Improving Student’s Reading Comprehension Through Listen-Read-Discuss (LRD) Strategy - Azifa, Alisa Azaefa; Hatip, Moch.; Laeli, Anita Fatimatul (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
Reading comprehension is a fundamental skill in learning English as a foreign language, but students often experience difficulties in learning texts due to limited vocabulary and lack of engagement strategies. This classroom action research study aims to improve students' reading comprehension by implementing the Read-Listen-Discuss strategy. The research was conducted at SMA Muhammadiyah 02 Wuluhan Jember with 22 students from class XI A. The research was conducted in two cycles consisting of planning, implementation, observation and reflection. The data was collected through student reading comprehension test and class observation. And the results of this study showed a significant improvement in students' reading performance. The average score increased from 65.15% to 76% with 75% of students achieving the minimum standard score of 70 by the end of the second cycle. This shows that the LRD strategy is proven to be effective in improving students' reading comprehension in learning activities.